(untitled) (Research, Society and Development, 2021)
Objective: To analyze the sociodemographic profile of individuals with depressive symptoms and suicidal behavior in a general adult population. Method: Exploratory-descriptive, quantitative study. Interviews with questionnaires and psychometric scales for depression in a general adult population in Poços de Caldas / MG. Results: Of 200 participants, 73 (36.5%) had depressive symptoms, 62 (84.92%) with previously diagnosed depression, 27 (37.0%) moderate intensity, 11 (15.1%) severe; 57 (78.1%) women, 22 (30.1) between 29-39 years, 67 (91.78%) white, 47 (64.4%) Catholics, 39 (53, 42%) married, 32 ( 43.8%) with up to 02 children, 20 (27.39%) incomplete primary education, 51 (69.86%) employed, 34 (46.58%) individual income up to 02 minimum wages; 39 (53.43%) lived with a partner / husband / wife / children; 23 (31.50%) lived in an area of ​​social vulnerability; 40 (54.8%) had clinical comorbidities; 30 (41.1%) with time since diagnosis of depression between 0 and 5 years; 54 (73.97%) reported treatment, of which 36 (66.7%) between 0 and 5 years old, 10 (18.5%) between 12 and 17 years old; 26 (35.61%) with suicidal ideation, 13 (50.0%) in the last 5 years, 11 (42.3%) did not report treatment, and of the 15 (57.7%) who reported treatment, 06 ( 40%) performed it in the last 03 months, with 07 (46.7%) only on medication and 03 (11.5%) the treatment was psychiatric hospitals. Conclusion: Prevalence of depressive symptoms in the study population (36.5%) was higher than the national average, with moderate / severe prevalence of symptom intensity. Participants with no previous symptoms presented greater severity of depressive symptoms, being women, unemployed, young people, low education and low income, with family members or the same with mental disorders, alcohol / drug users or chronic diseases.